Characteristics of Patients with Type 2 Diabetes Mellitus in Al-Ihsan Regional General Hospital - Siti Annisa Devi Trusda; Wida Purbaningsih; Budiman Budiman; Siti Salma Nurhaliza Fitriadi (Global Medical & Health Communication (GMHC), 2021)
The prevalence of type 2 diabetes mellitus (T2DM) in Indonesia is high, contributing to the fourth mortality rate for non-communicable diseases in Indonesia. The population of T2DM patients spread across all provinces, including West Java, which is the most populous province in Indonesia. One of the referral hospitals in West Java is Al-Ihsan Regional General Hospital in Bandung regency. The purpose of this study was to describe the characteristics of T2DM patients who came to Al-Ihsan Regional General Hospital according to age, gender, and comorbidities parameters. It was a descriptive cross-sectional study using secondary data from medical records of T2DM patients between January 2017 and November 2020. The results were the highest prevalence and incidence of T2DM were in 2017 with as many as 5,051 and 653 respectively; the highest gender each year was female, range between 584–3,333, with the highest male: female ratio of 1:2 in 2017; the age group with the highest prevalence was 55–65 years which was 3,468 (39.53%); and top five comorbidities were hypertension (35.68%), cataracts (6.01%), osteoarthritis (3.58%), pulmonary tuberculosis (2.92%) and dyspepsia (2.91%). This study concluded that the prevalence and incidence of T2DM in Al-Ihsan Regional General Hospital were high, with the predominant female patients, elderly, and comorbid hypertension. KARAKTERISTIK PASIEN DIABETES MELITUS TIPE 2 DI RSUD AL-IHSANAngka kejadian diabetes melitus tipe 2 (DMT2) di Indonesia cukup tinggi, menyumbangkan angka kematian keempat penyakit tidak menular di Indonesia. Penderita DMT2 tersebar di seluruh provinsi, termasuk Jawa Barat yang merupakan provinsi terpadat di Indonesia. Salah satu rumah sakit rujukan di Jawa Barat adalah RSUD Al-Ihsan di Kabupaten Bandung. Tujuan penelitian ini adalah menggambarkan karakteristik pasien DMT2 yang datang ke RSUD Al-Ihsan dilihat dari usia, jenis kelamin, dan komorbid. Penelitian ini merupakan penelitian deskriptif cross-sectional menggunakan data sekunder berupa rekam medis pasien DMT2 periode Januari 2017 hingga November 2020. Didapatkan bahwa prevalensi dan insidensi DMT2 tertinggi pada tahun 2017 sebesar 5.051 dan 653 masing-masing; jenis kelamin terbanyak pada setiap tahun adalah wanita sebesar 584–3.333 dengan rasio pria:wanita tertinggi 1:2 pada tahun 2017; kelompok usia dengan prevalensi tertinggi adalah 55–65 tahun sebesar 3.468 (39,53%); dan lima komorbid tertinggi adalah hipertensi (35,68%), katarak (6,01%), osteoartritis (3,58%), tuberkulosis paru (2,92%), dan dispepsia (2,91%). Simpulan penelitian ini adalah prevalensi dan insidensi DMT2 di RSUD Al-Ihsan tinggi dengan pasien terbanyak wanita, lanjut usia, dan komorbid hipertensi.